2015
DOI: 10.1519/jsc.0000000000000661
|View full text |Cite
|
Sign up to set email alerts
|

Caloric Expenditure of Aerobic, Resistance, or Combined High-Intensity Interval Training Using a Hydraulic Resistance System in Healthy Men

Abstract: Although exercise regimens vary in content and duration, few studies have compared the caloric expenditure of multiple exercise modalities with the same duration. The purpose of this study was to compare the energy expenditure of single sessions of resistance, aerobic, and combined exercise with the same duration. Nine recreationally active men (age: 25 ± 7 years; height: 181.6 ± 7.6 cm; weight: 86.6 ± 7.5 kg) performed the following 4 exercises for 30 minutes: a resistance training session using 75% of their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 15 publications
1
20
0
2
Order By: Relevance
“…RST performed for sets and repetitions in our study is considered a form of high intensity exercise (9), these findings support such a view and suggest that ST may be considered high intensity. Carbohydrate expenditure was significantly elevated during both ST and RST when compared to resting, this is consistent with other research on high intensity exercise which has demonstrated it is primarily fuelled by glycogen (9). Carbohydrate expenditure has been shown to increase as exercise intensity increases (27).…”
Section: A C C E P T E Dsupporting
confidence: 90%
“…RST performed for sets and repetitions in our study is considered a form of high intensity exercise (9), these findings support such a view and suggest that ST may be considered high intensity. Carbohydrate expenditure was significantly elevated during both ST and RST when compared to resting, this is consistent with other research on high intensity exercise which has demonstrated it is primarily fuelled by glycogen (9). Carbohydrate expenditure has been shown to increase as exercise intensity increases (27).…”
Section: A C C E P T E Dsupporting
confidence: 90%
“…Although it has been noted that there was also one study where HIIT burnt 25-30% more calories during the session doing 20 sec maximum effort 40 sec rest for 30 minutes -for 10 minutes actual work -compared to 30 minutes resistance training at 75 % of their 1RM, endurance cycling and endurance treadmill at 70% HRmax (Falcone et al, 2015) this hasn't been repeated elsewhere and could be attributed to the fact that recreationally active participants performed the exercises, not sedentary people and also to the unusually high number of work intervals in the protocol. Trapp et al, (2008) also found that 15 weeks of all-out HIIT three times a week for 20 minutes was superior to endurance work for reducing subcutaneous and abdominal fat mass in inactive women ( Figure 3).…”
Section: Weight Managementmentioning
confidence: 99%
“…For further field studies a higher number of participants and longer supervised times are needed to get really meaningful data and narrower confidence intervals (Heydari et al, 2012) (Figure 5). Even though it's a difficult form of exercise, those who adhered to it tend to score higher on the Physical Activity Enjoyment Scales (PAES) (Falcone et al, 2015;Kong et al, 2016;Roy et al, 2018).…”
Section: Hiit In a Real-world Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, many studies were conducted to evaluate burning more calories according to newer aerobic devices in traditional forms of aerobic exercise [9][10][11][12], and walking methods (modified forms of walking versus regular walking or walking versus running) [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%